The Effectiveness of Progressive Muscle Relaxation and Five-Finger Hypnotherapy (HP Majar) in Reducing Depression Levels in Patients with Mental Disorders - Kusladi, Aulia Meyda; Sholikhah, Siti; Saifudin, Moh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Mental disorders involve disturbances in a person's thoughts, behaviors, and emotions. If left untreated, mental disorders, such as depression, can become a serious issue. This study aimed to evaluate the effectiveness of progressive muscle relaxation and five-finger hypnotherapy in reducing depression levels among individuals with mental disorders. The research used a Pre-Experimental design (Two group pre-test and post-test design) with 52 participants selected through Consecutive Sampling. The interventions were conducted four times over the course of one week. Depression levels were measured before and after the intervention using the Beck Depression Inventory II. Data analysis was performed using the Wilcoxon Test and the Mann Whitney Test. The Wilcoxon Test revealed a significant effect for both progressive muscle relaxation therapy (p = 0.003) and five-finger hypnotherapy (p = 0.000). The Mann Whitney Test showed no significant difference in the effectiveness between the two therapies, with a p-value of 0.274 (p > 0.05). Both therapies were effective in reducing depression levels among patients with mental disorders. In conclusion, five-finger hypnotherapy proved to be more effective in reducing depression compared to progressive muscle relaxation therapy in individuals with mental disorders